Attribution, Interpretation, and Integrity in Online Research-Based Communications - Mark Anderson-Wilk; Ariel Ginsburg (Journal of Applied Communications, 2012)
Communicators have a role as standard setters in developing research-based land-grant public education products. This paper presents a rationale for communicators to help authors of public education materials understand the importance of attribution in their role as interpreters of research for their target audiences. It is also important for authors of public education materials to understand and follow best practices in documenting reference sources. These concepts are important not just in traditional publications but also when working in new media and online formats.
Keywords: attribution; creative integrity; research-based public education; science communication